Kegiatan Pendidikan dan Pengajaran Shalat Bagi Anak Pada Desa Palanjungan Sari Kecamatan Banjang, Kabupaten Hulu Sungai Utara - Barkatillah; M Alec Al-Amin; Norhidayah (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Prayer education for children plays an important role in forming the spiritual and ethical foundations of Muslim society from an early age. In Palanjungan Sari Village, Banjang District, Hulu Sungai Utara Regency, prayer teaching activities for children face specific challenges related to the availability of teachers and varied and effective learning methods. However, research related to the effectiveness of prayer teaching approaches in this village environment is still limited, so a more in-depth study is needed to assess the right approach to improve children's understanding of prayer. This study used a qualitative method with a case study approach to understand the process of prayer education for children, including in-depth interviews with teachers and observations of activities in the field. The results showed that interactive teaching methods based on direct practice proved to be more effective in building children's skills and understanding related to prayer implementation. In addition, the presence of parents in the prayer education process also had a positive impact on children's involvement in this activity. Support from the community and schools also became important factors that increased the success of this program. This study implies that the synergy between practical teaching methods, family support, and the surrounding environment can improve the quality of religious education for children in remote villages.